Prognostic criteria of chronic myeloid leukemia by changes platelets sizes. - Y. V. Shorop; A. S. Tymchenko (Medičnì Perspektivi, 2016)
In order to identify specific changes in the size of platelets in patients with chronic myeloid leukemia (CML) and assess possibility of their use as prognostic criteria for disease progression peripheral blood of 62 patients with CML was examined. The study was carried out by an automatic hematology analyzer and method of computer image analysis on micrographs of peripheral blood smears. CML patients showed an increase in mean platelet volume (parametr MPV) and the percentage of large platelets (parameter P-LCR). Measurement of platelet digital micrographs, carried out in parallel, showed an increase of variability of their size. Analysis of characteristic curves of the specificity/sensitivity showed the possibility of using the coefficient of variation and standard deviation of the natural logarithm of platelets in areas of the peripheral blood smear as a predictor of progression of CML in blast crisis phase.